2020
DOI: 10.1021/acs.nanolett.0c02417
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Chirality in Two-Terminal Electronic Nanodevices

Abstract: Central to spintronics is the interconversion between electronic charge and spin currents, and this can arise from the chirality-induced spin selectivity (CISS) effect. CISS is often studied as magnetoresistance (MR) in two-terminal (2T) electronic nanodevices containing a chiral (molecular) component and a ferromagnet. However, fundamental understanding of when and how this MR can occur is lacking. Here, we uncover an elementary mechanism that generates such an MR for nonlinear response. It requires energy-de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
127
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(133 citation statements)
references
References 41 publications
3
127
3
Order By: Relevance
“…Equation 3 agrees with the nonlinear MR discussed in Refs. 17 , 33 which are based on a symmetry analysis without considering the microscopic mechanism of CISS. Equation 3 agrees with the general nonlinear I-V profile and explains the MR due to flipping the lead magnetization in experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Equation 3 agrees with the nonlinear MR discussed in Refs. 17 , 33 which are based on a symmetry analysis without considering the microscopic mechanism of CISS. Equation 3 agrees with the general nonlinear I-V profile and explains the MR due to flipping the lead magnetization in experiments.…”
Section: Discussionmentioning
confidence: 99%
“…(iv) The dephasing related to the inelastic process was frequently discussed as a necessary condition 12 14 , 17 , 33 to generate CISS. The single-mode leads employed in these models prohibit the spin current in the presence of TRS 44 .…”
Section: Methodsmentioning
confidence: 99%
“…Previously, it was reported that a self-assembled monolayer of three-dimensional chiral DNA molecules could possess spin-polarized conduction electrons depending on the molecular chirality, which is generally called the CISS. The CISS has been confirmed in terms of various phenomena, such as circular polarization of light 14 , magnetoresistance effect 15,31 , moleculeadsorption-induced magnetization switching 16 , anomalous Hall effect 17 , and separation of enantiomers by a ferromagnet 18 . In these studies [14][15][16][17][18][19] , the CISS is explained in terms of the spin polarization of conduction electrons induced by the steady (or transient) current in the molecule.…”
mentioning
confidence: 81%
“…57 At the same time, progress is being made in terms of operation principles and design guidelines for chirality-based spintronic nanodevices and technologies. 66 A better understanding and design of these chiral molecular materials will pave the way for obtaining organic spintronic devices where the neuromorphic features could be adjusted by molecular design.…”
Section: Challenges In Theoretical Modelling Of Ciss and Spin Dynamics In Metallopeptidesmentioning
confidence: 99%